Structural, electronic, linear, and nonlinear optical properties of undoped and Mo (I, II)-doped LiNbO3 crystal - Abdul-Hussein, W. A; Almusawe, A. J (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
In this paper, density functional theory (DFT) calculations used to investigate the structural, electronic, linear and nonlinear optical properties of pure lithium niobate crystal (LiNbO3) and doped LiNbO3 by Mo (I) and Mo (I). The lattice constants were calculated by analysing the optimised unit cell, and the results were found to be in good agreement with both the experimental and theoretical values that were reported. The results indicate a clear distinction in the electronic characteristics of LiNbO3 and doped LiNbO3 (Mo-Nb), the band structures that have been computed indicate that the band gap of LiNbO3 can be narrowed by adding Mo (I) and Mo (II) dopants to 2.068 eV and 0.476 eV, respectively. Interesting results were obtained by this doping process, as these results showed that the effect of doping led to an improvement in some optical properties, such as the absorption spectrum of the material, and also led to an increase in the effect of second harmonic generation (SHG), which is considered a basic requirement for developing optical devices in many photonic applications such as laser, electro-optic applications and optical switches.